The Influence of Leadership and Supervision on Teacher Professionalism with Motivation as an Intervening Variable in MTs. Muhammadiyah 3 Kisaran - Fitriani, Fitriani; Alfahmi, Muhammad; Farida Ferine, Kiki (International Journal of Social Science, Education, Communication and Economics, 2024)
This research aims to determine the influence of leadership and supervision on teacher professionalism with motivation as an intervening variable in MTs. Muhammadiyah 3 Ranges. Furthermore, this research is quantitative research with descriptive methods. Based on the research results, it is known that the results of the validity test on variables X1, Furthermore, in the reliability test, the Cronbach's alpha value for each variable is greater than the specified significance value (X1 = 0.651, Z = 0.823, Y = 0.647 > 0.6), indicating that all items are reliable. Then the normality test shows that the value of Asymp.Sig. in the variables X1 = 0.19, The coefficient of determination test shows that the leadership, supervision, and motivation variables have an influence on the teacher professionalism variable of 0.475 or 47.5%.In the partial test, the Tcount results obtained for variables X1 = 4.188, X2 = 3.865, Z = 9.874 are greater than Ttable = 2.025. Shows that the dependent and intervening variables have a partial influence on the dependent variable.